Prospects for Growth and Jobs in the Palestinian Economy : A General Equilibrium Analysis - World Bank Group (World Bank, Washington, DC, 2017)
A large number of studies in recent years have attempted to analyze and quantify the myriad of restrictions holding back economic development in the West Bank and Gaza, but the full picture remains blurred. The main value proposition of this study is to assess and quantify the overall prospects for growth and jobs in the West Bank and Gaza using a Computable General Equilibrium model and taking into consideration the uncertain and dynamic environment of shifting boundaries, including the broader economic benefits that could be achieved with an alleviation of external and internal constraints. It is important to acknowledge that the external and domestic environments are in some cases interdependent. The study analyzes a number of different scenarios related to both external and internal constraints. Given the political realities, it is particularly important to study what Palestine could do on its own to improve growth prospects. The hope is that this study could help the Palestinian authorities and other stakeholders form a vision for inclusive, job-led growth and establish policy priorities depending on the evolution of the geo-political environment. The study provides an outline of such a vision, drawing on the findings of the scenarios discussed above and could be further developed by incorporating the findings from the parallel Vision pieces under way in trade and energy. Further, the study should help inform the Bank’s strategic and operational engagement with Palestine by highlighting key reforms and investments needed to support higher and more inclusive growth.